1980
DOI: 10.1104/pp.65.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Some New Aspects of the in Vivo Assay for Nitrate Reductase in Wheat (Triticum aestivum L.) Leaves

Abstract: Experiments were carried out to clarify problems encountered in measuring metabolic and storage pool sizes of nitrate in wheat leaf sections with an in vivo nitrate reductase assay. The leaf sections were from seedlings grown on 15 millilar nitrate. Data obtained show that the cessation of nitrite accumulation, used as an index of the active nitrate pool size, could be caused by lack of anaerobiosis in the assay system, the lack of energy for nitrate reduction, or a loss of nitrate reductase activity. Availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

1981
1981
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 10 publications
0
23
1
Order By: Relevance
“…In contrast, Ferrari et al (8) observed that most of the nitrate was still present in tobacco cells as cessation in nitrite production was approached. However, Hageman et al (9) have shown recently that the system used by Ferrari et al (8) probably was not completely anaerobic, and cessation of nitrite production could have been caused by the lack of complete anaerobiosis in the assay system. The presence of 02 in the system of Ferrari et al (8) may have not only prevented the leakage of nitrate from tobacco cells (6) but also inhibited nitrate reduction (4,15), thus causing apparent cessation in nitrite production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Ferrari et al (8) observed that most of the nitrate was still present in tobacco cells as cessation in nitrite production was approached. However, Hageman et al (9) have shown recently that the system used by Ferrari et al (8) probably was not completely anaerobic, and cessation of nitrite production could have been caused by the lack of complete anaerobiosis in the assay system. The presence of 02 in the system of Ferrari et al (8) may have not only prevented the leakage of nitrate from tobacco cells (6) but also inhibited nitrate reduction (4,15), thus causing apparent cessation in nitrite production.…”
Section: Discussionmentioning
confidence: 99%
“…The method was first proposed by Ferrari et al (8), who observed that nitrate reductase activity and energy supply for nitrate reduction were not factors limiting nitrite production in tobacco cells. Hageman et al (9) observed that, in wheat leaves, nitrite production could be stopped by the lack of energy and loss of nitrate reductase activity. Nitrate availability within the tissue is not considered to be limiting to nitrite production (8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper the need for complete anaerobiosis for estimation of NR activity based on nitrite accumulation has been shown by Hageman et al (1980). In this study we have followed the method of Nicholos et al (1976).…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not imply that root biomass was the several years in field conditions. only controlling factor of N03 uptake, as Chevalier and Schrader Hageman et al (10) reported that they were unable to estimate (7) supply. This is in agreement with a previous study (21).…”
Section: Resultsmentioning
confidence: 95%